A mineralogical study of pigments used in two Iakovidis paintings: Verification of artwork authenticity using Raman micro-spectroscopy method. - Kougemitrou, I.; Economou, G.; Giovanopoulos, J.; Baziotis, I.; Leontakianakos, G.; Stathopoulos, V. (Bulletin of the Geological Society of Greece, 2013)
For the purpose of the current study, we examined two paintings, an original and a fake one, entitled “Still life with grapes”, and claimed both to be created from the Greek Painter G. Iakovidis. The current Research Project has been carried out at the Centre Nikias, an innovative Research Centre specialised on certification, maintenance and restoration of art works. Raman spectroscopic analysis has been carried to verify the authenticity of the used pigments and also the originality of the two paintings. The Raman spectra acquired confirmed four different colours in both painting`s pigments: red, blue, white and yellow. For the first painting Cinnabar for the red pigment, Ultramarine for the blue pigment, White earths for the white pigment and Yellow ochre for the yellow pigment. In the second painting the colours used verified as synthetic pigments. We identified the presence of Cadmium red for the red colour, Cobalt blue for the blue pigment, Zinc white for the white and Cadmium yellow for the yellow one.